Identification of local isolates of the genus Bacillus and testing their effectiveness in the laboratory against the two-spotted spider mite Tetranychus urticae Koch. - حسن, لمى; اميمة ناصر ,; ماجدة مفلح, (Latakia University Journal -Biological Sciences Series, 2025)
Isolation of Bacillus subtilis from the local soil in Lattakia Governorate, the bacterial isolates were characterized by some characteristics based on their Gram staining, some biochemical properties and depending on the color characteristics on specific and selective cultures. The isolates were tested against the Koch red two-spotted spider. Tetranychus urticae, under laboratory conditions, on stages (egg, nymph, and adult). The results of the tests showed that the isolates had a significant effect on the egg stage, as the concentration of 107 cells / ml gave the highest mortality rate of 78 %, with a significant difference from the rest of the treatments. Mortality in other stages was (38-82) % for larvae, (37-80) % for nymphs of the first age, (37-78) % for nymphs of the second age, and (35-74) % for adult females. The control mortality rates ranged between (0-7) % for larvae, (2-8) % for first-instar nymphs, (2-11) % for second-instar nymphs, (5-8) % and (4-6) % for adult females.